Epithelioid trophoblastic tumor (ETT) initially interpreted as cervical cancer. Issue 4 (1st June 2003) - Narita, F.; Takeuchi, K.; Hamana, S.; Ohbayashi, C.; Ayata, M.; Maruo, T.
Abstract : The epithelioid trophoblastic tumor (ETT) is a rare form of trophoblastic disease and shows a wide spectrum of differential diagnoses and clinical behavior. A 53-year-old woman presented with ETT presumably originated in spontaneous delivery of 25 years ago and was initially diagnosed as cervical cancer on cervical punch biopsy followed by radical hysterectomy. The uterus showed a small tumor restricted to the cavum with no cervical infiltration, resembling ETT in histologic and immunohistochemical features. The difficulties and clues in distinguishing ETT from nontrophoblastic lesions are discussed.